TENG-Bot: Triboelectric nanogenerator powered soft robot made of uni-directional dielectric elastomer. (July 2021) - Sun, Wenjie; Li, Bo; Zhang, Fei; Fang, Chunlong; Lu, Yanjun; Gao, Xing; Cao, Chongjing; Chen, Guimin; Zhang, Chi; Wang, Zhong Lin
Abstract: A soft robot employing dielectric elastomer actuators (DEAs) exhibits a flexible body and dexterity locomotion in unstructured environments. However, conventional power supplies required by DEAs pose an obstacle for small-scale robotic system. Triboelectric nanogenerator (TENG) is capable of harvesting kinetic energy from the environment to generate matching power for DEA. Yet, a TENG-driven, DEA-based robot is hindered due to the nonlinear and insufficient mechanical transmission in robotic motion. In this paper, we developed an uni-directional DEA-driven soft robot. It aligns the direction of DEA in extension with the robot motion to achieve high efficient energy conversion, yielding a maximum crawling velocity of 110 mm (2.2 body-length) /sec and a payload capacity of 40 g. Then a TENG-Bot, that is a TENG-soft robot conjunction system, is built using a freestanding TENG. With the benefit from the simple structure, and the high efficiency of the robot, the electrical energy generated by the TENG can directly drive the robot without additional control panels. Experiments demonstrate a linear relationship between the sliding speed of the TENG and the velocity of the soft robot, a direct control correspondence. The TENG-Bot offers a route for developing self-powered soft robots by harvesting the environment motion. Graphical Abstract: ga1 Highlights: TENG-Bot, that is a TENG-soft robot conjunction system, is built using a freestanding TENG, where the electrical energy generated by the TENG can directly drive the robot without additional control panels. A uni-directional DEA-driven soft robot is developed that aligns the direction of DEA in extension with the robot motion to achieve high efficient energy conversion. Linear relationship between the sliding speed of the TENG and the velocity of the soft robot is attained, offering a route for developing self-powered soft robots by harvesting energy in motion.